A low flow-high flow investigation into the effect of selected micronutrients on pre-determined innate immune biomarkers in two freshwater fish species from Witbank dam, Mpumalanga - Radzuma, Murendeni Unarine Sandra (My University, 2025)
The aquatic environment is constantly in jeopardy since it is the ultimate recipient of waste disposal. Mining, industrial and agricultural developments have led to a significant increase in, amongst others, heavy metal contamination in aquatic systems. The aim of this study was to use seasonal surveys to investigate the impact of Fe, Cu, and Zn levels on immune modulation in Cyprinus carpio and Micropterus salmoides collected from Witbank Dam, Mpumalanga. This study consisted of two surveys that were conducted during low flow periods in June and high flow periods in November. Temperature, pH, dissolved oxygen, conductivity, total dissolved solutes (TDS) and salinity were measured using YSI multiparameter instrument. A litre of water and sediment samples were collected from three different sites, while 26 common carp and 12 largemouth bass were sampled using conventional fishing gear. For each fish, the weight and length were measured. Furthermore, epidermal mucus and blood samples were collected. Serum and mucus samples were divided, half was treated with PBS and the other with protease inhibitor cocktail and stored at -20°C until further analysis. Gills, liver, and muscle tissue were dissected, weighed, rinsed, and frozen at -85°C for later analysis of Fe, Cu, and Zn levels by Waterlab (Pty) Ltd, Pretoria. From the results, it was discovered that Witbank dam is polluted by Cu and Zn. Furthermore, Cu concentrations were only detected in the liver of both common carp and largemouth bass. Iron and zinc were detected in varying concentrations across tissues, with Fe levels being highest in the liver and gills, particularly in largemouth bass, and Zn levels being highest in the gills of common carp. The use of the protease inhibitor cocktail was found to significantly preserve CRP levels, with treated samples showing higher concentrations compared to untreated samples, indicating its effectiveness in preventing protein degradation. The study highlights the need for pre-analytical care in feral studies to ensure accurate biomarker measurements and highlights the seasonal fluctuations in metal exposure, which could influence immune responses in fish. The recommendations of the study include implementing regular monitoring of metal concentrations in aquatic ecosystems and considering the use of protease inhibitors in future studies involving immune biomarkers. The study was limited to a small sample size and one sampling area.
Thesis (M.Sc. (Physiology)) -- University of Limpopo, 2025
Keywords: Biomarker; Immune; Ecosystems; Waste disposal; Micronutrients; Innate; Freshwater; Fish species; Biochemical markers; Fresh water; Groundwater -- Pollution; Heavy metals -- Environmental aspects; Heavy metals -- Analysis